PREVENTIVE ROLE OF ZINC CHLORIDE AGAINST TOXICITY OF CIPROFLOXACIN ON THE GROWING CARTILAGE OF WISTAR ALBINO RAT LITTER - Channa, Haji Muhammad Aslam; Ashfaq, Muhammad; Bangash, Rahim; Abbasi, Abdullah; Qureshi, Muhammad Azam (Journal of Ayub Medical College Abbottabad, 2008)
Objective: To assess the preventive role of zinc chloride on toxicity of ciprofloxacin administration in wistar albino rat litter. It was a Prospective experimental study. The study was carried out in the department of Anatomy, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi, Pakistan during March 2002 to February 2003 one year study. Method: Ciprofloxacin and zinc chloride were administered to newly born albino rat litters separately and simultaneously at a dose of 20 mg/kg body weight and 1200 ïg/Kg body weight respectively, intraperitonealy twice daily from 1-14 day after birth. The animals were sacrificed by deep ether anaesthesia. The fore and hind limbs were dis-articulated from the axial skeleton, soft tissue was removed and bones were fixed in 10% buffered formalin. Decalcification was done in 10% nitric acid and 10% formic acid changes. After paraplast embedding, 4ïm thick longitudinal sections of proximal & distal ends of long bones were cut by a rotary microtome. Routine staining with haemotoxylin and eosin was performed. Histomorphometery was done to measure the thickness of epiphyseal cartilage and was compared with similar values of the control animals. The results were statistically analyzed to evaluate the significance. Result: Our study revealed that ciprofloxacin administration in new born albino rat litter decreased the width of epiphyseal growth plate cartilage by 13.7±0.42 ïm, 10.43% in humerus and 6.6±1.2 ïm 4.72% in femur as compared to control, whereas, simultaneous zinc chloride administration restricted the decrease to 1.27 ïm±SD in humerus and 2.05 ïm±SD in femur. Conclusion: Simultanous zinc chloride administration minimized the epiphseal cartilage damage induced by ciprofloxacin in Wistar albino rat litter. Keywords: Ciprofloxacin, Cartilage toxicity, Cartilage growth, Zinc chloride, Epiphyseal growth plate, Growth rate, Chondrocyte.